1992
DOI: 10.1038/bjc.1992.386
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbogen breathing on tumour tissue oxygenation in man evaluated by computerised p02 histography

Abstract: Summary Tumour tissue oxygenation has been measured in man during carbogen breathing (95% 02, 5% C02) using a commercially available polarographic electrode system (Eppendorf P02 histograph). At least 200 tumour measurements in each of 17 patients with accessible tumours were taken before, and subsequently continuously after the commencement of carbogen breathing for periods of 10 to 30 min. In 12 out of 17 patients studied there was a significant increase in median tumour P02 during the first 10 min of carbog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 16 publications
7
37
0
1
Order By: Relevance
“…Each individual was therefore assessed separately, and nine out of ten showed significant rises in tumour oxygen distribution. As in our previous study of carbogen breathing alone (Falk et al, 1992), we found a wide range of change in median p02 with elimination of some but not all values of p02 below 5 mmHg. The rises in median pO2 tended to be of greater magnitude than in the previous study and were sustained until 15 min and over in the majority of our patients, whereas in the previous study a fall in median tumour pO2 occurred in all patients between 12 and 18min.…”
Section: Dimsciosupporting
confidence: 58%
“…Each individual was therefore assessed separately, and nine out of ten showed significant rises in tumour oxygen distribution. As in our previous study of carbogen breathing alone (Falk et al, 1992), we found a wide range of change in median p02 with elimination of some but not all values of p02 below 5 mmHg. The rises in median pO2 tended to be of greater magnitude than in the previous study and were sustained until 15 min and over in the majority of our patients, whereas in the previous study a fall in median tumour pO2 occurred in all patients between 12 and 18min.…”
Section: Dimsciosupporting
confidence: 58%
“…The time-course of the response was in the range of previous studies using carbogen to oxygenate tumors (41,47), although longer breathing periods (60 min) have been reported to be required in EMT6 human tumor xenografts (47). In normal brain, a plateau in PtO 2 in response to changes in oxygen or CO 2 is reached within 5 minutes (27).…”
Section: Oxygen Response With Carbogen Breathingmentioning
confidence: 60%
“…A breathing time dependence of the improvement in tumour oxygenation of clinical tumours. as measured by Po2 distribution using microelectrodes, has also been observed (Falk et al, 1992); the greatest improvement in oxygenation was seen after 8-12 min breathing and it decreased as breathing continued. This suggests that similar compensation mechanisms may be operating in human tumours.…”
Section: Resultsmentioning
confidence: 78%